Wahbah Zuhaili’s and Sayyid Sabiq’s Perspective on The Principles of Marriage Contract in Indonesia - Hafidzi, Anwar; Mohd. Hani, Mohd Hatta (al-'adalah, 2020)
This study discusses pronunciations used in marriage contracts in Indonesia with various types of pronunciation. The jurisprudence experts agree to use the words "Nikah and Kawin" in a marriage contract because it is based on Q.S Al-Azhab verse 37 which uses the word "Nikah". This study tries to compare the use of these words in the book of Fiqh al-Islam wa Adillatuh by Wahbah Zuhaili and Fiqh al-Sunnah by Sayyid Sabiq. The results showed that the marriage pronunciations used were based on meaning, not pronunciation, provided that there was an intention or indication for marriage and was understood by the witnesses. Therefore, according to Wahbah Zuhaili, using a word other than what has been stipulated in the text of the Al-Qur'an is still valid. Meanwhile, Sayyid Sabiq stated that the pronunciation of the contract must be in words that can be understood by each party and must not use vague words.